Design of Prototype Temperature and Humidity Control System for Oyster Mushroom Barns Integrated with ThingsBoard for Real-Time Monitoring - Riko Adytia Anggara; Budi wibowo; Muhamad Riko Arafi; Mudrika Afdila (Jurnal Komputer dan Elektro Sains, 2025)
Oyster mushrooms grow optimally at 24-27°C and 80-95% relative humidity. Environmental conditioning through manual spraying water in the mushroom barn in the morning and evening is considered less effective and requires high effort. The application of technology in mushroom cultivation can help control temperature and humidity automatically. This study aims to design an automatic control system to regulate temperature and humidity in oyster mushroom farms. The research was conducted at an altitude of 125 meters above sea level with an automatic control system that has a setpoint temperature of 24-27 ° C and humidity of 80-95%. The test was conducted in a 4 × 2 × 2 m mushroom barn with a capacity of 600 mushroom bag logs. The performance test results showed that the daily temperature and humidity without control ranged from 24.10-35.19 °C and 64.28-99.90%. In contrast, with automatic control, daily temperature and humidity were recorded between 25.10-30.09 °C and 80.84-99.90%. This study shows that the automatic control system Effectively maintains optimal environmental conditions for oyster mushroom growth.